MOTIVASI REMAJA MENJADI RELAWAN PADA ORGANISASI FORUM ANAK KABUPATEN SERANG - Muhammad Rafli Nurdianto; Ahmad Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the motivation of adolescents to become volunteers in the Serang Regency Children's Forum (FAKS), identify obstacles that influence this motivation, and describe the organization's strategy in increasing the participation of its members. The main focus of this study is to understand how this non-profit organization managed by children under the guidance of the government is able to maintain the active involvement of adolescents without any material imbalance. The research method used is descriptive qualitative. Data were collected through participant observation, unstructured interviews with 7 informants (consisting of daily administrators and division coordinators), and documentation studies. Data analysis was carried out through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that: (1) Adolescent motivation is dominated by intrinsic and non-material factors, where physical (financial) needs have shifted in meaning to become operational support instruments, while social needs and being awarded are the strongest factors. (2) Motivational obstacles include internal obstacles such as low self-esteem (self-doubt) and failure of self-regulation, as well as external obstacles in the form of negative stigma in the social environment. (3) The organizational strategy implemented is strengthening social support networks, modernizing activity methods, and facilitating access to learning resources. This study concludes that the sustainability of motivation in the Children's Forum is largely determined by the organization's ability to provide space for self-actualization and psychological protection for its members.